In vitro drug sensitivity profile and characterization of Escherichia coli isolated from diarrhoeic chicken in Kashmir valley - WANI, S A; BHAT, M A; SAMANTA, I (The Indian Journal of Animal Sciences, 2014)
In all 71 faecal samples from diarrhoeic chickens revealed the presence of 38 strains of E, coli, Thirty two strains belonged to 16 different serogroups (08,09,010.014,019,025,051. 065, 069, 089, 091m 0104, 0106, 0120, 0157 and 0164), while as remaining 6 strains were untypable, The 08 serogroup of E. coli was the most prevalent serogroup. Twenty six strains belonging to 13 serogroups (08, 09, 010, 019, 025, 069, 089, 091,0104,0106,0120, 0157 and 0164) were considered pathogenic because of their ability to bind congo red dye, However, 10 strains belonging to 9 differentserogroups (08, 09,014,025,051,065,069,091 and 0120) were unable to bind congo red dye, Out. of 38 studied only 1 was found haemolytic, All vitro sensitivity profile revealed that the majority of isolates were sensitive to gentamicin and ampicillin/cloxacillin, All isolates were resistant to penicillin, tetracycline, erythromycin, nitrofurantoin, streptomycin and sulphamethazine that necessitates the need for judicious use to antibiotics.